PHYTOCHEMICAL SCREENING, ANALGESIC ACTIVITY, AND ANTIDEPRESSANT ACTIVITY OF THE METHANOL EXTRACT OF GAULTHERIA FRAGRANTISSIMA WALL. IN WISTAR RATS - NONGKHLAW, FREDDY TEILANG; C, MALSAWMTLUANGI; LAPASAM, PHAIBIANG; LALTHASANGA, ANDREW (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was undertaken to screen the analgesic and the antidepressant activity of Gaultheria fragrantissima Wall. an ethnomedicinal plant of Meghalaya, India. Methods: In this study, the analgesic effect was induced by hot plate method and tail immersion test. The analgesic effect of two doses of the methanolic extract of Gaultheria fragrantissima Wall. was tested and diclofenac was used as a standard drug. The antidepressant activity was brought about by force swimming test and tail suspension test. The antidepressant effect of two doses of the methanolic extract of G. fragrantissima Linn. was tested and imipramine was used as a standard drug. The statistical analysis was carried out by one-way analysis of variance (ANOVA) followed by Tukey-Kramer multiple comparison tests using GraphPad InStat 3.0 software. Results: The analgesic study shows that the plant extract at two different doses (200 mg/kg and 400 mg/kg) possesses significant analgesic activity (p<0.01), whereby the two different doses of the plant extract showed a significant increase in the latency time were obtained at 120 min in hot plate method and increase in the latency time were obtained at 90 min in the tail immersion method, respectively. The antidepressant study shows us that the methanolic extract at 200 and 400 mg/kg produced significant reduction (p<0.001) in the immobility period when compared with that of control group animals in both the tests. Conclusion: The result of the study shows that the methanolic bark extract of G. fragrantissima Wall. possesses analgesic activity and antidepressant activity.